Evidence Based Dentistry - Malik, Dr.Poonam; Rathee, Dr. Manu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
It has been fascinating to observe the discussions that have played out regarding evidence based dentistry. At one end of spectrum, some writers’ portray evidence-based care as revolutionary new approaches to dental care that will save our profession. Other describe it time consuming process. Through this review describes the basis behind the use of evidence based dentistry